The contribution of the Joseph case to the development of procedural fairness in the Republic of South Africa - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2016)
Mini Dissertation (LLM)--University of Pretoria, 2015.